Research on Bronze as a Vehicle for Chinese Writing - Yifan, Yan (Sinología hispánica. China Studies Review, 2025)
Bronze has always been an important representative of ancient Chinese civilization, and inscriptions on bronzes have attracted the research of domestic and foreign scholars. Generally, the classification of Chinese writing in the pre-Qin period is according to the writing materials. Hard materials mainly refer to bones, stone tools, ceramics and bronzes, and soft materials mainly include bamboo tablets, wooden tablets and silk. Writing instruments are divided into knife and pen. Inscribing on hard materials with a knife is called inscription, and writing on soft materials with a brush is called writing. From the Shang dynasty through the Spring and Autumn and Warring States periods, with economic, political and cultural changes, bronze changed from a means of communication between humans and gods to a symbol of political rights and then to a writing medium. Bronze inscriptions also went through different stages. This article focuses on the classification of inscribed bronzes and the evolution of the nature of bronze as a writing medium.